Analysis of WTO Dispute Settlement on Korea Alcoholic Taxes - Priska Suoth, Tirzha Carolaine; Polimpung, Reinaldy Putra; Kolondam, Daniel; Aipassa, Julio; Bryan Goni, Go Christian (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research aims to find out whether Korea violates the provisions of International trade Article III: 2 First sentence and second sentence of GATT in 1994. Soju is a traditional alcoholic beverage that is most famous in Korea has been produced in a diluted manner so that the beverage content of 25% alcoholic soju can be said that the beverage has a content that is below 20%. But people in European countries and the United States have complaints or opinions that they do not agree with the alcohol tax policy in South Korea, especially soju is considered unfair. So Korea is trying to offer a preference for taxes on soju drinks compared to certain imported western-style drinks. The research conclusions show that Soju and Imported Liquor Spirits are not substitutive products. Soju and Imported Liquor Spirits do not compete directly, seen from the fact that although there has been a decrease in the number of Soju sales in Korea since the ILS tax was lowered, the distance between Soju and ILS sales is still far away. So from the facts above, South Korea does not violate GATT Article III: 2 Second Sentence. From our explanation above, Like Products is a cumulative requirement to meet: Common Characteristics End Uses Channels of distribution Prices. From that data, South Korea does not violate GATT Article III: 2 First Sentence and Second Sentence although there are differences in tax imposition because the two products, Soju and ILS are not like products. Keywords: Soju, Alcohol Beverages, Tax